Aerodynamic optimization of winglets for an Unmanned Aerial Vehicle - Ivković Dušan; Kostić Ivan; Kostić Olivera; Dinulović Mirko; Simonović Aleksandar (Scientific Technical Review)
The main aim of this paper was to determine the influence of different parameters of winglet design on overall Unmanned Aerial Vehicle (UAV) aerodynamics. Looking from an aerodynamicist's point of view, the main reason for using such wingtip devices is to reduce induced drag component, which noticeably contributes to total drag when flying both in cruising flight and on higher angles of attack at lower speeds. Significant benefits of using winglets on overall aircraft performance include reduced fuel burn, increased maximum range and endurance, and higher cruise altitude. Total drag of a simplified mock-up of an existing tactical UAV was calculated using hybrid approach. Parasite drag was obtained using analytical and semi empirical methods, while the induced drag and the lift in its linear domain were determined using inviscid CFD model based on a 3D vortex lattice method (VLM). Computational analyses were focused on determining the influence of winglet cant angle, root chord length, span, airfoil, and twist angle on lift-to-drag ratio of the UAV. Results obtained for different types of winglets (straight, blended and elliptical) were compared, and the best performing in the prescribed dimensions were the elliptical winglets. Their geometry was further optimized, finally providing an overall lift-to-drag ratio increase of 7% compared to the original UAV design without winglets, which represents quite remarkable improvement.